2003
DOI: 10.1590/s1517-83822003000300017
|View full text |Cite
|
Sign up to set email alerts
|

Extra and intracelular activities of carbonic anhydrase of the marine microalga Tetraselmis gracilis (Chlorophyta)

Abstract: The activities of extra and intracellular carbonic anhydrases (CA) were studied in the microalgae Tetraselmis gracilis (Kylin) Butcher (Chlorophyta, Prasinophyceae) growing in laboratory cultivation. During ten days of batch cultivation, daily determinations of pH, cell number, enzymatic activity, and total dissolved inorganic carbon (DIC), as well as its main species, CO2 and HCO3 -, were performed. Enzymatic activity increased as the growing cell population depleted inorganic carbon from the medium. Carbon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Nonetheless, many species of microalgae can actively transport bicarbonate ions across the plasma membrane to the cytosol, where the intracellular activity of carbonic anhydrase maintains a steady flux of CO 2 to ribulose bisphosphate carboxylase oxygenase (RuBisCo) for photosynthesis. Alternatively, extracellular carbonic anhydrase (CA) can also catalyze the interconversion between HCO 3 − and CO 2 , which has been evidenced for photosynthetic microorganisms . With pH in the culture medium maintained at 7.3 ± 0.5, the dynamic equilibrium between bicarbonate and CO 2 also provides this gas to the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, many species of microalgae can actively transport bicarbonate ions across the plasma membrane to the cytosol, where the intracellular activity of carbonic anhydrase maintains a steady flux of CO 2 to ribulose bisphosphate carboxylase oxygenase (RuBisCo) for photosynthesis. Alternatively, extracellular carbonic anhydrase (CA) can also catalyze the interconversion between HCO 3 − and CO 2 , which has been evidenced for photosynthetic microorganisms . With pH in the culture medium maintained at 7.3 ± 0.5, the dynamic equilibrium between bicarbonate and CO 2 also provides this gas to the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Assay of CA activity was carried out electrometrically using a modified procedure of Wilbur and Anderson [45] as described by Rigobello-Masini et al [46]. For the preparation of the algal extract, the optical density of microalgal culture was measured spectrophotometrically at 560 nm and a culture aliquot of 2ml was centrifuged at 5708 RCF.…”
Section: Time Course Profile Of Dissolved Inorganic Carbon Species (Dmentioning
confidence: 99%
“…The preparation of algal extract and reaction was performed at low temperature (0-2 o C). The carbonic anhydrase enzyme activity was calculated by using the following equation [46].…”
Section: Time Course Profile Of Dissolved Inorganic Carbon Species (Dmentioning
confidence: 99%
“…eCA is constitutive in most of the marine phytoplankton, whereas the expression was regulated by the concentration of inorganic carbon (Nimer et al ; Elzenga et al ). Previous studies have shown that the activity of eCA in marine phytoplankton depends on the availability of inorganic carbon, light and the pH (Moroney et al ; Rigobello‐Masini et al ). Expression of eCA increased at low partial pressure of CO 2 (pCO 2 ) and light availability, but essentially the expression was reduced at conditions with higher pCO 2 .…”
mentioning
confidence: 99%